Consumers' preferences for carbon labels and the underlying reasoning. A mixed methods approach in 6 European countries. (20th March 2018) - Feucht, Yvonne; Zander, Katrin
Abstract: The present research explores whether carbon labels are an appropriate and effective tool for increasing climate-friendly food consumption in Europe. Using a mixed methods approach which combines choice experiments and a questionnaire with qualitative face-to-face interviews, the preferences and willingness to pay for carbon labels and claimed climate-friendliness are explored in six European countries. Our results show that the presence of a carbon label increases the purchase probability and that consumers are willing to pay a price premium of up to 20% for a carbon label in all countries included in the investigation. Regarding the design of a carbon label, a combination of a horizontal scale in traffic light like colors with an absolute number of CO2 -equivalents is preferred. But consumers are willing to pay higher price premiums for local products than for carbon labeled products in most study countries. They tend to subsume climate-friendliness together with local and/or organic production under the umbrella terms 'eco-friendly' and 'ethical behavior'. Since they lack knowledge and problem awareness with respect to climate-friendly consumption, consumers are frequently overstrained with respect to climate-friendly buying decisions. Consumers expect policy makers and retailers to set up appropriate structures to support climate-friendly consumption. Given this, the contribution of a carbon label to a more climate-friendly consumption might be limited without the structural support of policy makers and retailers. Highlights: Preferences and willingness to pay for carbon labels are explored in six European countries. Consumers are willing to pay a price premium for carbon labels. Label design with a horizontal scale and traffic light like colors is preferred. Consumers tend to subsume climate indications under the term 'eco-friendliness'. It is unlikely that the majority of consumers will actively consider carbon labels.